2018
DOI: 10.1002/ppul.24082
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase inhibitors: Potential role in the respiratory distress of neonates

Abstract: Phosphodiesterases (PDEs) are a superfamily of enzymes that catalyze the hydrolysis of phosphodiester bonds of 3',5' cyclic adenosine and guanosine monophosphate (cAMP and cGMP). PDEs control hydrolysis of cyclic nucleotides in many cells and tissues. Inhibition of PDEs by selective or nonselective PDE inhibitors represents an effective targeted strategy for the treatment of various diseases including respiratory disorders. Recent data have demonstrated that PDE inhibitors can also be of benefit in respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 77 publications
(110 reference statements)
0
9
0
Order By: Relevance
“…PDEs include different species subtypes with different affinities and specificities for different substrates. It has been shown [ 28 ] that the use of PDE inhibitors in addition to inhaled prostacyclin prolongs the duration of action of prostacyclin, improves haemodynamics, and does not affect systemic arterial blood pressure or gas exchange, but the long-term efficacy of PAH treatment with PDE inhibitors alone has not been demonstrated.…”
Section: Current Status Of Pah Treatment With Inhaled Formulationsmentioning
confidence: 99%
“…PDEs include different species subtypes with different affinities and specificities for different substrates. It has been shown [ 28 ] that the use of PDE inhibitors in addition to inhaled prostacyclin prolongs the duration of action of prostacyclin, improves haemodynamics, and does not affect systemic arterial blood pressure or gas exchange, but the long-term efficacy of PAH treatment with PDE inhibitors alone has not been demonstrated.…”
Section: Current Status Of Pah Treatment With Inhaled Formulationsmentioning
confidence: 99%
“…5 Potential candidates for targeting neonatal lung inflammation are phosphodiesterase (PDE) inhibitors, such as methylxanthines and their derivates. 8 Caffeine, a methylxanthine widely used in the treatment of apnea in preterm infants, has been shown to decrease the incidence of BPD. 9 Although the mechanism is still discussed, caffeine's property as a weak, non-specific PDE inhibitor might contribute to its beneficial effect on BPD.…”
Section: Introductionmentioning
confidence: 99%
“…Such a variety of physiological involvement inevitably suggests involvement in human pathology as well. Indeed, numerous reviews have showed evidence on PDE-mediated implications in such diseases, as cancer ( Peng et al, 2018 ), neurologic ( Halene and Siegel, 2007 ; Nthenge-Ngumbau and Mohanakumar, 2018 ; Gurney, 2019 ), inflammatory ( Page and Spina, 2011 ), pulmonary ( Fan Chung, 2006 ; Mokry et al, 2018 ; Joskova et al, 2020 ; Kawamatawong, 2021 ; Mokra and Mokry, 2021 ), pediatric ( Mokra et al, 2018 ), and cardiovascular disorders ( Ravipati et al, 2007 ), among others. Additionally, the PDE enzymes are characterized by several factors, including a high degree of isoform variation, a high degree of isoform specificity towards substrates, distinct tissue expression and subcellular localization patterns among different isoforms, and the generally favorable intracellular cyclic nucleotides’ concentration, that further highlight their potential as drug targets ( Bender and Beavo, 2006 ).…”
Section: The Cyclic Nucleotide Phosphodiesterase Superfamily—overviewmentioning
confidence: 99%